Correction of menopausal symptoms in patients with medical menopause - Сапожак, И. Н.; Богослав, Ю. П. (REPRODUCTIVE ENDOCRINOLOGY, 2013)
Gonadotropin-releasing hormone agonists (GnRH) used for long-term monotherapy or combination therapy for hormone-dependent tumors. However, their use leads to hypoestrogenism and to all manifestations of menopause. Therefore, patients receiving GnRH therapy, sometimes forced to give it up because of menopause symptoms. The use of GnRH agonists with phytoestrogens can improve the quality of patients’ life, reducing the negative symptoms of menopause. The study results showed that the treatment of endometriosis by GnRH agonists with phytoestrogen drug Lifemin® almost 5 times reduces the manifestation of psycho-emotional disorders, 8 times reduces vasomotor disorders and improves the skin condition.